Almost Periodic Discrete Sets - Favorov, S.; Kolbasina, Ye. (Журнал математической физики, анализа, геометрии, 2010)
We study the almost periodic discrete sets in R^k. Also, we show the connection between these sets and almost periodic measures and calculate their Fourier transform.